A positive plate for high-rate, long-cycle, high-safety lithium battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202210113775.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-01-30
Smart Images

Figure CN116565131B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a positive electrode sheet for high-rate, long-cycle, and high-safety lithium batteries, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have advantages such as high energy density, good cycle performance, long service life, low self-discharge, and no memory effect. They are gradually occupying a larger application market in energy storage, power batteries, and 3C electronics, and have broad application prospects.
[0003] Lithium-ion batteries are continuously being developed towards higher energy density to provide better range for electric vehicles, digital products, and other power electronic devices. Increasing the loading and compaction density of electrode plates, especially the positive electrode plate, is an effective way to improve battery energy density. However, as the loading and compaction density of the positive electrode plate increase, the active material layer thickens and the porosity decreases, making lithium-ion transport within the positive electrode plate difficult. This leads to severe battery polarization, a decrease in the battery's discharge specific capacity and rate performance, and a reduction in cycle stability. Simultaneously, as battery energy density increases, battery safety often becomes more difficult to guarantee. To date, no technology can simultaneously solve all of these problems.
[0004] Existing methods for improving battery rate performance include: Cathode surface doping: Patent application CN113224287A discloses a strontium-doped ternary lithium-ion battery cathode material (Li). 1-x Sr x [Ni 1-y-z Co y M z [O2, where M is one of metals Mn and Al, 0 < x ≤ 0.1, 0 < y ≤ 1, 0 < z ≤ 1) and its preparation method and applications. By doping lithium sites with strontium metal ions, the degree of cation mixing is reduced, lithium ion channels are expanded, and the layered structure is stabilized, effectively improving the rate performance of lithium batteries. However, while this method improves rate performance, it often leads to accelerated capacity decay.
[0005] Existing methods for improving battery safety performance include: Cathode Coating: Patent application CN113809280A discloses a cathode material and its preparation and application. By modifying the sintering technique and utilizing the interaction between the coating agent, a cathode material with a near-planar coating effect is prepared. The cathode material prepared by this method has a large surface coating coverage, significantly reducing the erosion of material particles by the electrolyte, effectively reducing the probability of side reactions, and thus improving material safety. Disadvantages: The method is complex and affects battery rate performance.
[0006] Existing methods for simultaneously improving battery electrical performance and safety performance: CN 108365260 B discloses a quasi-solid-state electrolyte, the raw material composition of which includes a polymer, a ceramic electrolyte, a lithium salt, and an ionic liquid. The ceramic electrolyte comprises a main phase of lithium aluminum titanium phosphate and a heterogeneous phase of TiP2O7 / TiO2. Preferably, the heterogeneous phase content in the ceramic electrolyte is 2-7%, and the mass ratio of TiP2O7 to TiO2 is 1.5-2.5:1. The quasi-solid-state electrolyte prepared from the ceramic electrolyte with this heterogeneous phase content exhibits the best overall performance. The heterogeneous phase with this specific composition and content possesses lithium storage characteristics, which can improve lithium-ion transport performance and reduce the contact between the main phase of lithium aluminum titanium phosphate and metallic lithium, thereby improving the interfacial stability with metallic lithium. However, this patent does not improve the positive electrode's electrical performance and safety performance, and the method is incompatible with the mainstream preparation process of existing lithium-ion battery positive electrodes, making it unsuitable for large-scale applications.
[0007] CN113707880A relates to a positive electrode containing a solid electrolyte, its preparation method, and its application, aiming to improve the rate performance, cycle performance, and safety performance of batteries. The solid electrolyte in the positive electrode slurry facilitates the transverse and longitudinal transport and wetting of the electrolyte within the electrode, aiding in electrolyte storage and wetting. During cell cycling, it also helps alleviate electrode expansion, reducing the amount of electrolyte squeezed out under pressure, ensuring sufficient electrolyte within the electrode even after long-term cycling, thus guaranteeing normal lithium-ion transport and improving cycle performance. However, data from the embodiments show only a slight improvement in battery capacity and safety, with insufficient data to support the effect on rate performance. This indicates that adding conventional solid electrolytes cannot comprehensively improve battery electrical and safety performance.
[0008] CN113346066B discloses a polymetallic phosphate-coated lithium cobalt oxide cathode material and its preparation method. The invention suggests that the polymetallic phosphate coating layer on the surface of the lithium cobalt oxide cathode material matrix is a fast ion conductor, which can improve the material's rate performance. The coating layer can also prevent reactions between the electrode and the electrolyte, slowing down the capacity decay of the lithium cobalt oxide material. However, data from examples show that compared with the uncoated lithium cobalt oxide material, the increase in capacity after polymetallic phosphate coating, as well as the improvement in cycle performance, rate performance, and storage performance, are very limited (<10%). In particular, the improved rate performance is still not high and cannot meet the actual needs of power batteries.
[0009] It is evident that existing technologies, such as doping the positive electrode with a solid electrolyte or coating the positive electrode active material with a lithium-conducting layer, cannot simultaneously improve the rate performance, cycle performance, and safety performance of a battery, thus failing to meet the requirements of power batteries. Therefore, it is still necessary to find a simple and cost-effective method to simultaneously improve battery electrical performance and safety performance. Summary of the Invention
[0010] To address the limitations of existing technologies, our strategy is to redesign the CEI (Chemical Electrode Injection) on the positive electrode surface, leveraging the synergistic effect of the multifunctional components of the CEI to improve its efficiency, thereby comprehensively enhancing the rate performance, cycle performance, and safety performance of the battery. Furthermore, we prepare a safety coating on the surface of the positive electrode, which further contributes to improving battery safety performance. This invention provides a high-rate, long-cycle, high-safety positive electrode for lithium batteries, its preparation method, and its applications. The positive electrode of this invention includes a positive electrode material layer and a functional layer directly located on the positive electrode material layer.
[0011] The functional layer includes component 1, which is selected from LiM12(PO4)3 and Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x One or more of (PO4)3, wherein M1 is selected from one of Ti, Ge, Zr and Hf, and 0 < x < 0.6; Component 1 is preferably Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.4 Al 0.4 Ge 1.6 One of (PO4)3, LiTi2(PO4)3, and LiGe2(PO4)3; The functional layer includes component 2, which is selected from M1O2 and Li. 16-4y M1 yAt least one or more combinations of O8, M1P2O7, M2PO4, M32SiO5, M23(PO4)2, and M32SiO4, wherein M2 and M3 are one of Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, and Ge, and wherein 3 <y<4; Component 2 is preferably one of InPO4, AlPO4, Al2SiO5, TiO2, and TiP2O7.
[0012] The mixed component form of component 1 and component 2 in the functional layer can be a uniform mixture between component 1 particles and component 2 particles, or each primary particle can contain both component 1 crystal form and component 2 crystal form.
[0013] The functional layer is a three-dimensional porous structure with a porosity of p, where 20% ≤ p ≤ 80%, and a thickness of h, where 0 μm < h ≤ 10 μm.
[0014] The particle size of component 1 is 10 nm to 10 μm. Preferably, the particle size of component 1 is 50 nm to 1 μm.
[0015] The particle size of component 2 is 10 nm to 10 μm. Preferably, the particle size of component 2 is 50 nm to 1 μm.
[0016] Preferably, the positive electrode active material particles are selected from at least one of lithium cobalt oxide positive electrode and its modified materials, NCM ternary positive electrode and its modified materials, NCA ternary positive electrode and its modified materials, lithium nickel manganese oxide positive electrode and its modified materials, lithium-rich positive electrode and its modified materials, and lithium iron phosphate positive electrode and its modified materials. The conductive agent is selected from at least one of Super-P, KS-6, carbon black, carbon nanofibers, carbon nanotubes, acetylene black, or graphene. The binder is selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, homopolymers, copolymers, modified compounds of the above polymers, or mixtures of the above polymers and other polymers or small molecules.
[0017] A second objective of this invention is to provide a method for preparing a positive electrode sheet for lithium batteries, as described in one of the objectives of this invention. The mixed component of component 1 and component 2 is used to form a functional layer on the surface of the positive electrode by coating. A slurry comprising the mixed component of component 1 and component 2 is coated onto the surface of the positive electrode sheet, and the mixed component of component 1 and component 2 forms a coating on the positive electrode surface and is dispersed among the positive electrode active material particles.
[0018] Preferably, the preparation method includes the following steps: Step 1: Prepare the positive electrode active layer; Step 2: Mix the mixture of component 1 and component 2 with the solvent until homogeneous, and grind it into a slurry with solid particles of 10nm-10um; Step 3: Add binder to the slurry obtained in Step 2 and mix evenly to prepare a coating slurry; Step 4: Coat the slurry obtained in Step 3 onto the positive electrode active layer and dry it to obtain the positive electrode sheet.
[0019] Preferably, In step two, The solvent used in the slurry is at least one selected from deionized water, ethanol, NMP, alcohol, isopropanol, and acetone. The mass ratio of the solvent to the cathode material is (2000-10):100.
[0020] In step four, The temperature of the blower drying is 80-180℃, and the time is 10 minutes to 9 hours; the temperature of the vacuum drying is 80-180℃, and the time is 3-100 hours.
[0021] A third objective of this invention is to provide the application of the positive electrode sheet described in one objective of this invention in lithium batteries.
[0022] The lithium battery is either a liquid battery or a solid battery.
[0023] This invention coats a functional layer onto the surface of a positive electrode using a surface coating method. The functional layer contains a mixture of Component 1 and Component 2, with a particle size D50 of 0.01-10µm, which improves the rate performance, cycle performance, and safety performance of the battery. The technical principle is as follows: First, Component 1, possessing lithium-ion conductivity and containing variable-valence transition metal elements (Ti, Ge), exhibits optimal effect. This type of additive can form a continuous network, which is beneficial for electrolyte storage and wetting, significantly improving the conductivity of lithium ions at the positive electrode. In particular, Component 1 is compatible with the positive electrode CEI, improving the mechanical stability of the CEI and forming a superior CEI / electrolyte interface. Component 2 can suppress unstable, low-ionic-conductivity CEI generated by electrolyte decomposition. The combined use of Component 1 and Component 2 has a synergistic effect, generating a more stable CEI with stronger lithium-ion conductivity, which is connected to the lithium-ion conduction network within the positive electrode. This significantly reduces interfacial resistance and polarization during battery operation, significantly improving the battery's rate performance, surpassing existing technologies. Furthermore, synergistic design can also solve the thermal runaway problem caused by CEI instability, thereby comprehensively improving the rate performance, cycle performance, and safety of the positive electrode. The aforementioned synergistic effect cannot be achieved by adding component 1 or component 2 alone. If only component 1 is added, although it can connect the CEI to the lithium-ion transport network in the electrolyte, battery polarization will still occur if the electrolyte continuously decomposes to produce a CEI with low lithium-ion conductivity. If only component 2 is added, without the mechanical strength enhancement provided by component 1, the CEI is prone to breakage, and the electrolyte will decompose at the breakage point. Therefore, component 2 is often needed to fully coat the active material to inhibit electrolyte decomposition, reducing production efficiency. With component 1 strengthening the CEI, only a small amount of component 2 is needed to effectively inhibit electrolyte decomposition, which is the advantage of the synergistic effect. Furthermore, when the mixture of components 1 and 2 forms a coating on the electrode surface, the coating not only separates the positive and negative electrodes to prevent short circuits within the battery, but also improves lithium-ion conduction in the direction parallel to the positive electrode surface and reduces electrolyte decomposition on the positive electrode surface by improving the CEI of the positive electrode surface layer. This is because the positive electrode surface is the area with the most sufficient contact with the electrolyte, and protecting the positive electrode surface can most effectively improve battery performance. Introducing additives into the positive electrode through surface coating does not change the current mainstream manufacturing processes of positive electrodes, separators, and batteries, and helps to improve the rate performance of the battery. It has the advantages of high stability and low cost, making it suitable for large-scale applications.
[0024] Compared with the prior art, the present invention has the following advantages and outstanding effects: The mixed component particles of component 1 and component 2 in the functional layer on the surface of the lithium battery cathode of this invention exhibit high chemical stability. They can be added to the cathode after cathode preparation via surface coating, without altering the current mainstream manufacturing processes for cathodes, separators, and batteries. This ensures compatibility with existing mainstream manufacturing processes for lithium-ion battery cathodes and does not affect the manufacturing processes of the cathode and battery cells. It offers advantages such as high stability and low cost, making it suitable for large-scale applications. In contrast, methods of cathode material doping or cathode surface coating require changes to existing cathode material preparation technologies, making it difficult to simultaneously improve discharge specific capacity and rate performance.
[0025] This invention utilizes a mixed component of component 1 and component 2 to achieve a synergistic effect, constructing a superior CEI that significantly improves the rate performance of the battery, while also enhancing its cycle performance and safety performance. It is the optimal choice for solving the main existing problems of current power batteries.
[0026] While existing technologies, such as the combination of solid electrolyte and oxide, can improve the ionic conductivity of the cathode, the mixed composition of component 1 and component 2 in this invention achieves a stable CEI with faster lithium-ion conduction, making it more suitable for both liquid and solid-state batteries, especially when an electrolyte is present. Existing technologies generally prefer solid electrolytes with high ionic conductivity when using solid electrolyte doping to improve the cathode, while this invention prefers a solid electrolyte compatible with CEI, which can more effectively improve rate performance, as low interfacial transport is a key factor hindering the performance of electrolyte-based batteries. Existing technologies generally use common high-temperature resistant ceramics such as Al2O3 when using oxides to improve the cathode, while this invention prefers compounds that inhibit electrolyte decomposition to improve CEI conductivity and stability, allowing for more precise suppression of thermal runaway. Through the ingenious design of this invention, the synergistic effect of component 1 and component 2 is achieved. After optimizing component 1, only a small amount of component 2 needs to be coated to achieve better results than existing technologies that use component 2 to coat the cathode material, thus improving production efficiency.
[0027] The mixture of components 1 and 2 forms a safety coating on the surface of the positive electrode, which can isolate the positive and negative electrodes and improve battery safety. Experiments have shown that batteries with this safety coating do not catch fire or explode during hot-box testing because the safety coating can prevent short circuits by isolating the positive and negative electrodes. The safety coating not only isolates the positive and negative electrodes to prevent internal short circuits, but also improves lithium-ion conduction in the direction parallel to the positive electrode surface and reduces electrolyte decomposition on the positive electrode surface by improving the CEI (Chemical Electrolyte Intake) of the positive electrode surface layer. This is because the positive electrode surface is the area with the most sufficient contact with the electrolyte; protecting the positive electrode surface is the most effective way to improve battery performance.
[0028] The porosity of the functional layer on the lithium battery positive electrode sheet of this invention is specially designed. If the porosity is less than 20%, it is detrimental to the battery's rate performance; if the porosity is greater than 80%, it is detrimental to the battery's cycle performance. The thickness of the functional layer is also specially designed. If the coating thickness is greater than 10 μm, it is detrimental to the battery's rate performance. The positive electrode exhibits excellent rate performance, cycle performance, and safety. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 1; Figure 2 This is a schematic diagram of the lithium battery heavy object impact test fixture of the present invention; Figure 3 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 9. Detailed Implementation The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0030] Example 1 Step 1: Prepare the NCM positive electrode active layer, with an active material mass of 100g; Step 2: Add 25 kg of component 1 Li 1.4 Al 0.4 Ti 1.6 The mixture of (PO4)3 and component 2 AlPO4 was mixed with 500 kg NMP and ground into a slurry with a D50: 300 nm; the content ratio of component 1 to component 2 was 4:1. Step 3: Add 1 kg of PVDF to the slurry obtained in Step 2 and stir evenly to prepare a coating slurry; Step 4: Coat the slurry obtained in Step 3 onto the NCM90 positive electrode active layer, and dry it to obtain the positive electrode sheet with a coating thickness of 1μm and a porosity of 40%.
[0031] A schematic diagram of the positive electrode structure for lithium batteries prepared by the above method is shown below. Figure 1As shown, the electrode includes a current collector 5, a positive electrode material layer on the current collector 5, and a functional layer 3 directly on the positive electrode material layer. The positive electrode material layer includes a positive electrode active material 4, a conductive agent, and a binder. The functional layer 3 includes component 1 particles 1 and component 2 particles 2. The component 1 particles and component 2 particles in the functional layer 3 are uniformly distributed, and some component 1 particles and component 2 particles diffuse into the positive electrode material layer and are distributed between the particles of the positive electrode active material 4. A soft-pack lithium battery is assembled using this positive electrode sheet and matched with a SiOC650 negative electrode. After the prepared lithium battery undergoes liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. Specific electrochemical performance test results are shown in Table 1, and safety performance test results are shown in Table 2.
[0032] The lithium battery electrochemical performance testing methods used in this application are as follows: 1. Cyclic performance testing a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) The battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. c) Repeat steps a and b until the discharge capacity is less than 80% of the discharge capacity in the first cycle, and record the total number of battery cycles at this point.
[0033] 2. Ratio Test a) At 23 ℃±2 ℃, the battery was charged to the charging termination voltage at rates of 0.1 C, 0.2 C, 0.33 C, 1 C, 2 C, and 3 C, respectively, and then discharged to the discharge termination voltage at the same rate. Each cycle was repeated 4 times at the same rate. b) Record the discharge capacity at different discharge rates; c) Calculate the ratio of 2C or 3C discharge capacity to 0.33C discharge capacity, denoted as 2C / 0.33C or 3C / 0.33C, to evaluate rate performance.
[0034] 3. High-temperature cycling a) Charge at a constant current of 1 C at 45 °C until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, then stop charging; b) Let the battery stand at 45 ℃ for 5 h; c) Under high temperature of 45 ℃, the battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. d) Repeat steps a to c until the discharge capacity is less than 80% of the discharge capacity of the first cycle. Record the discharge capacity of the battery and the total number of cycles at this point.
[0035] Lithium-ion battery safety performance testing methods: 1. Overcharging a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Charge the battery at a constant current of 1 C until thermal runaway occurs, and record the battery voltage value when thermal runaway begins.
[0036] 2. Hot box a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place the battery in the test chamber. The test chamber is heated at a rate of 5 °C / min, and the temperature is maintained at 160 °C ± 2 °C for 1 hour. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0037] 3. Fall a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Free fall from a height of 1m onto a concrete slab; Each side of the pouch battery was dropped once, for a total of six tests. After six tests, the battery is considered to have passed if it does not smoke, catch fire, or explode; otherwise, it is considered to have failed.
[0038] 4. Impact of heavy objects a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place battery 8 on the platform surface, and place a metal rod 9 with a diameter of 15.8 mm ± 0.2 mm horizontally on the upper surface of the battery's geometric center. Use a weight of 9.1 kg ± 0.1 kg to freely drop from a height of 610 mm ± 25 mm onto the surface of the battery with the metal rod placed on it, and observe for 6 hours. A schematic diagram of the weight impact test fixture is shown below. Figure 2 10 is the traction rope, 6 is the guide tube, and 7 is the steel impact box (the hinge door is not shown).
[0039] The soft-pack battery is required to undergo impact testing only on its wide side, and each sample must undergo only one impact test. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0040] 5. Acupuncture a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Using a φ8mm high-temperature resistant steel needle (with a cone angle of 45° at the needle tip, and a smooth surface free of rust, oxide layer and oil), insert the needle at a speed of 25 mm / s from a direction perpendicular to the battery plate, with the insertion point being the geometric center of the pierced surface, and the steel needle remaining in the battery. c) Observe for 1 hour; The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0041] Example 2 Component 1 replaced with Li 1.4 Al 0.4 Ge 1.6 (PO4)3 was used, with the positive electrode active material replaced by NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0042] Example 3 Component 1 was replaced with LiTi2(PO4)3, component 2 with Ti3(PO4)4, the positive electrode active material was replaced with NCM83, and the negative electrode was replaced with SiOC450. The battery structure was NCM83||SiO450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0043] Example 4 Component 1 was replaced with LiGe2(PO4)3, component 2 was replaced with Ca3(PO4)3, the positive electrode active material was replaced with LCO, and the negative electrode was replaced with SiOC450. The battery structure was LCO||SiO450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0044] Example 5 Component 2 was replaced with LaPO4, the positive electrode active material was replaced with LFP, and the negative electrode was replaced with graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0045] Example 6 Component 1 replaced with Li 1.4 Al 0.4 Ge 1.6 (PO4)3, component 2 is replaced with FePO4, the positive electrode active material is replaced with NCM83, and the negative electrode is replaced with graphite. The battery structure is NCM83||graphite, and other parameters are the same as in Example 1. The lithium batteries prepared above were subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0046] Example 7 The positive electrode porosity was replaced with 80%, and other parameters were the same as in Example 1. The prepared lithium battery was then subjected to electrochemical and safety performance tests after liquid injection, formation, and capacity testing. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0047] Example 8 The positive electrode porosity was replaced with 20%, and other parameters were the same as in Example 1. The prepared lithium battery was then subjected to electrochemical and safety performance tests after liquid injection, formation, and capacity testing. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0048] Example 9 The cathode coating thickness is replaced with 500 nm. Each primary particle of the mixed component contains particles of both the first and second component crystal forms. The particle size D50 of the primary particles of the mixed component is 300 nm. The mixing form of component 1 and component 2 is as follows: Figure 3 As shown, 11 is a mixture of components 1 and 2 in one particle, 3 is the functional layer, 4 is the active material, and 5 is the current collector. Other parameters are the same as in Example 1. After the prepared lithium battery is subjected to liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0049] Example 10 The positive electrode coating thickness was replaced with 10 μm, and other parameters were the same as in Example 1. The prepared lithium battery was then subjected to electrochemical and safety performance tests after liquid injection, formation, and capacity testing. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0050] Example 11 The positive electrode porosity was replaced with 20%, and the D50 of the primary particles constituting the mixed component of components 1 and 2 was replaced with 50 nm. Other parameters were the same as in Example 9. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0051] Example 12 The D50 of the primary particles constituting the mixed component of components 1 and 2 was replaced with 1 μm, and other parameters were the same as in Example 9. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0052] Example 13 The D50 of the primary particles constituting the mixed component of components 1 and 2 was replaced with 50 nm, and the thickness of the positive electrode coating was replaced with 10 nm. Other parameters were the same as in Example 9. After the lithium battery prepared above underwent liquid injection, formation, and capacity testing, electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0053] Comparative Example 1 Component-free 1 and Component-free 2, with other parameters the same as in Example 1; the lithium batteries prepared above were subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0054] Comparative Example 2 Component 1 and Component 2 were used, with the positive electrode active material replaced by NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0055] Comparative Example 3 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by NCM83 and the negative electrode by SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0056] Comparative Example 4 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by LCO and the negative electrode being SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0057] Comparative Example 5 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by LFP and the negative electrode being graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0058] Comparative Example 6 Component 1 and Component 2 were omitted, the positive electrode active material was replaced with NCM83, the negative electrode was graphite, and the battery structure was NCM83||graphite. Other parameters were the same as in Example 1. The lithium batteries prepared above were subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0059] Comparative Example 7 The mixed component consisting of 25 kg of component 1 and component 2 was replaced with 25 kg of Al2O3, while other parameters remained the same as in Example 1. The prepared lithium battery underwent electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0060] Comparative Example 8 The mixed component consisting of 25 kg of component 1 and component 2 was replaced with 25 kg of ZnO, and the positive electrode active material was replaced with NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0061] Comparative Example 9 Replace the mixed component consisting of 25 kg of component 1 and component 2 with 25 kg of Li. 1.4 Al 0.4 Ti 1.6 The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0062] Comparative Example 10 The mixed component consisting of 25 kg of component 1 and component 2 was replaced with 25 kg of AlPO4, the positive electrode active material was replaced with LCO, and the negative electrode was replaced with SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0063] Comparative Example 11 Replace the mixed component consisting of 25 kg of component 1 and component 2 with 25 kg of Li. 0.5 La 0.5 TiO3 was used, with the positive electrode active material replaced by LFP and the negative electrode replaced by graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0064] Comparative Example 12 The mixed component consisting of 25 kg of component 1 and component 2 was replaced with 25 kg of Li7La3Zr2O. 12The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. After the prepared lithium battery underwent liquid injection, formation, and capacity testing, electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0065] Table 1 shows the electrochemical performance data of the examples.
[0066] Table 1
[0067] Table 2 shows the safety performance data of the embodiments.
[0068] Table 2
[0069] As shown in Tables 1 and 2, coating the positive electrode surface with a mixed-component functional layer consisting of component 1 and component 2 can significantly improve the rate performance, cycle performance, and safety performance of the battery. A comparison between Example 3 and Comparative Example 9 shows that coating the positive electrode with a functional layer is far more effective in improving the battery's rate performance, cycle performance, and safety performance than coating the positive electrode surface with a high lithium-ion conductivity solid electrolyte. This is because constructing an efficient CEI is key to improving the electrical and safety performance of liquid and hybrid solid-liquid batteries. A comparison between Example 4 and Comparative Example 10 shows that coating the positive electrode with a functional layer is far more effective in improving the battery's rate performance, cycle performance, and safety performance than coating the positive electrode surface with phosphate to inhibit electrolyte decomposition. The difference in improving battery electrical performance between the two examples is particularly significant. This is because constructing a high lithium-ion conductivity CEI and connecting the CEI with the lithium-conducting network in the electrolyte is crucial, which cannot be achieved by simply coating the positive electrode surface with phosphate. A comparison of Examples 1 with Examples 7 and 8 shows that the porosity of the functional layer on the lithium battery cathode sheet of the present invention has an optimal design. If the porosity is too small, it is detrimental to the battery's rate performance; if the porosity is too large, it is detrimental to the battery's cycle performance. A comparison of Examples 1 with Examples 9, 10, and 13 shows that the functional layer has an optimal thickness. If the thickness is too small, it is detrimental to safety performance; if the thickness is too large, it is detrimental to rate performance. A comparison of Examples 1 with Examples 11 and 12 shows that components 1 and 2 have optimal particle sizes. Optimizing the particle size can improve the battery's electrical performance and safety performance. If the particle size is too small, the additive particles are prone to agglomeration, affecting rate performance and cycle performance; if the particle size is too large, the additive particles cannot fully contact the surface of the active material particles, especially affecting rate performance and safety performance. Both excessively small and excessively large particle sizes are detrimental to the construction of a stable CEI.
[0070] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A lithium battery positive electrode sheet, the positive electrode sheet comprising a positive electrode material layer and a functional layer directly located on the positive electrode material layer, characterized in that: The functional layer includes component 1, which is selected from LiM12(PO4)3 and Li 1+x Al x Ti2 x (PO4)3, Li 1+x Al x Ge2 x One or more of (PO4)3, wherein M1 is selected from one of Ti, Ge, Zr and Hf, and 0 < x < 0.6; The functional layer includes component 2, which is selected from Li 16-4y M1 y At least one or more combinations of O8, M1P2O7, M2PO4, M32SiO5, M23(PO4)2, and M32SiO4, wherein M2 is one of Sc, Y, Ca, Sr, Zn, Si, Lu, La, Fe, Cr, and Ge, and M3 is one of Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, and Ge, wherein 3 <y<4; The functional layer has a three-dimensional porous structure with a porosity of p, where 20% ≤ p ≤ 80%. Components 1 and 2 in the functional layer are uniformly distributed, and some of Components 1 and 2 diffuse into the positive electrode material layer and are distributed between the particles of the positive electrode active material.
2. The lithium battery positive electrode sheet according to claim 1, characterized in that: Component 1 is Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.4 Al 0.4 Ge 1.6 One of (PO4)3, LiTi2(PO4)3, and LiGe2(PO4)3; And / or, component 2 is one of Al2SiO5, FePO4, LaPO4, Ca3(PO4)3, Ti3(PO4)4, and TiP2O7; And / or, in the functional layer material, the mixed component of component 1 and component 2 is a uniform mixture between component 1 particles and component 2 particles, or each primary particle contains both component 1 crystal form and component 2 crystal form.
3. The lithium battery positive electrode sheet according to claim 1, characterized in that: The thickness of the functional layer is h, where 0 μm < h ≤ 10 μm.
4. The lithium battery positive electrode sheet according to claim 1, characterized in that: The particle size of component 1 in the functional layer is 10 nm-10 μm.
5. The lithium battery positive electrode sheet according to claim 3, characterized in that: The particle size of component 1 in the functional layer is 50 nm-1 μm.
6. The lithium battery positive electrode sheet according to claim 1, characterized in that: The particle size of component 2 in the functional layer is 10 nm-10 μm.
7. The lithium battery positive electrode sheet according to claim 1, characterized in that: The particle size of component 2 in the functional layer is 50 nm-1 μm.
8. The lithium battery positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes at least one of lithium cobalt oxide positive electrode and its modified material, NCM ternary positive electrode and its modified material, NCA ternary positive electrode and its modified material, lithium nickel manganese oxide positive electrode and its modified material, lithium-rich positive electrode and its modified material, and lithium iron phosphate positive electrode and its modified material.
9. A method for preparing a lithium battery positive electrode sheet according to any one of claims 1-8, characterized in that, Includes the following steps: Step 1: Prepare the positive electrode active layer; Step 2: Mix the mixture of component 1 and component 2 with the solvent until homogeneous, and grind it into a slurry with solid particles of 10nm-10μm; Step 3: Add binder to the slurry obtained in Step 2 and mix evenly to prepare a coating slurry; Step 4: Coat the slurry obtained in Step 3 onto the positive electrode active layer and dry it to obtain the positive electrode sheet.
10. The preparation method according to claim 9, characterized in that: The solvent includes one of deionized water, ethanol, NMP, isopropanol, and acetone.
11. A lithium battery cell, characterized in that: The lithium battery cell includes a positive electrode, a negative electrode, a separator, an electrolyte, and a casing, wherein the positive electrode is the positive electrode as described in any one of claims 1-8.
12. The lithium battery cell according to claim 11, characterized in that: The lithium battery can be either a liquid battery or a solid battery.
Citation Information
Patent Citations
A quasi-solid-state electrolyte, its preparation method and application
CN108365260B
Strontium-doped ternary lithium ion battery positive electrode material, and preparation method and application thereof
CN113224287A
A phosphate-coated lithium cobalt oxide cathode material and its preparation method
CN113346066B
Positive pole piece containing solid electrolyte, and preparation method and application thereof
CN113707880A
Positive electrode material and preparation and application thereof
CN113809280A